Neurofilament Light Chain (NF-L) Stimulates Lipid Peroxidation to Neuronal Membrane through Microglia-Derived Ferritin Heavy Chain (FTH) Secretion. (24th March 2022) - Gong, Li; Yu, Qiuyue; Wang, Haichao; Xu, Chenhaoyi; Dou, Yunxiao; Mao, Bingjie; Zhao, Yanxin
Abstract : A part of the axonal cytoskeleton protein complex, neurofilament light chain (NF-L) has been suggested as a pathological hallmark in various neurological disorders, including hemorrhagic stroke, vascular dementia, and cerebral small vessel disease. Neuroaxonal debris are mainly engulfed and phagocytosed by microglia, while the effects of NF-L on microglia have not been elucidated. Ferritin heavy chain (FTH) not only reflects the age-related status of microglia but may also be secreted into the extracellular space. After treatment of microglia with varying concentrations of NF-L (0-3  μ g/ml), we found robust increases in the number of secretory FTH-containing exosomes in the medium. Induction of the FTH-containing exosomes secreted from microglia stimulates neuronal loss and membrane lipid peroxidation, as assessed by CKK8 and C11-Bodipy 581/591, respectively. However, this oxidative stress damage was attenuated by blocking Fth1 expression. Our results suggest that NF-L, as a biomarker of axonal injury itself, could participate in neuronal ferroptosis in a nonclassical manner by secreting FTH-containing exosomes from microglia into the extracellular matrix.